The Urgency of E-Da’wa in The Digital Age - Awaludin Pimay; Uswatun Niswah (Lentera: Jurnal Ilmu Dakwah dan Komunikasi, 2021)
The rise of the digital era has changed almost all sectors of human life today. This is related closely to the rapid development of various internet-based digital media. Da'wah activities as one of the necessary steps to color all sectors of life with Islamic values ​​certainly need to take advantage of this development effectively and efficiently so that the objectives of da'wah can be achieved more easily. This paper aims to highlight the urgency of e-da'wah in the digital era as the ideal response of the da'i to the development of communication and information technology which has a direct impact on various ways and methods of carrying out da'wah. This research is a literature study that analyzes several articles in various popular and scientific media that discuss da'wah, information and communication, and internet technology. The results of the study indicate that several internet-based media can be used in implementing e-da'wah, such as websites, blogs, mailing lists, social media, and virtual meeting applications. Many da'wah media in this digital era need to be packaged creatively, innovatively, and adaptively to remain relevant amid rapid technological developments in recent decades.